Vadose Zone Monitoring as a Key to Groundwater Protection - Dahan, Ofer (Frontiers in Water, 2020)
Monitoring programs designed for groundwater protection are based today mainly on information from observation wells. This however creates a paradox, since identification of pollution in well water is clear evidence that the groundwater is already polluted. The poor state of contaminated aquifers all over the world, and the inability in practice, to fully remediate contaminated aquifers, suggest that groundwater monitoring alone has failed to provide the vital information required to prevent groundwater pollution. That said, groundwater pollution initiates on land surface, and the contaminants have to traverse the unsaturated zone, long before reaching the water table. Therefore, monitoring programs which can provide real-time information on the hydraulic and chemical state of the unsaturated zone, are essential for achieving early warnings on pollution potential, and providing imperative protection from pollution hazards. Currently, most of the commercially available monitoring technologies are rather limited in their capability to provide early alerts on pollution processes taking place deep in the unsaturated zone, above the water table. Accordingly monitoring technologies for the unsaturated zone have to be engineered as “off-the-shelf” commercial products, made available for application by practitioners in all fields of hydrology. From scientific and technological points of view, such ambitions are not out of reach. Yet they require an urgent call for a revolutionary shift in monitoring focus, from the groundwater itself to the unsaturated zone above it.